Design and Analysis of Static Composite Fuel Storage Tanks Alignment with ASME Section X - Nureddin Omar Fahel Alboum; Najeeb A Yahya; Mustafa A Essury; M A Elfaghi, Abdulhafid (International Journal of Integrated Engineering, 2025)
The increasing demand for lightweight, corrosion-resistant fuel storage solutions has increased the interest in composite pressure vessels; however, their industrial adoption remains limited due to the lack of standardized design frameworks under international codes. This study presents a structured approach for designing and validating an ASME Section-X, compliant composite fuel storage tank using E-glass fibers and vinyl ester resin. The research addresses the absence of scalable methodologies by integrating analytical modeling, hybrid manufacturing strategies, and finite element analysis (FEA) for structural validation. A vertical fuel storage tank was developed with detailed calculations, and design requirements are achieved according to Class II structural requirements under the ASME Section X safety factor guidelines (2.5× burst pressure). The hybrid fabrication method combined ±55° filament winding for hoop stress optimization with hand lay-up for localized reinforcement at nozzle connections and stiffener zones. Structural performance was evaluated using FEA in ANSYS Workbench, focusing on stress distribution, deformation behavior, and buckling sensitivity under operational loading. Simulation results confirmed a safe mechanical response, with effective stress transfer and reduced local concentration through bonded contact and layered material definition. Reinforcement strategies significantly improved joint efficiency and load redistribution.